Psychology'S Love–Hate Relationship with Love: Critiques, Affirmations, and Christian Responses - Tjeltveit, Alan C. (Journal of psychology and theology, 2006)
Christian psychologists’ contributions to understanding love of God and neighbor have fallen far short of their potential. A major reason, I argue, is psychologists’ love–hate relationship with love. Psychologists raise challenging questions about love (or some understandings of love), based on their (usually implicit) ethical intuitions (e.g., that telling battered women to love their abusers harms them). In addition, some understandings of love (e.g., pertaining to obligations, choices, and/or divine action) fit poorly with psychology's natural scientific methods. On the other hand, psychologists conduct research relevant to love and most psychologists seem deeply committed to love. Psychologists thus both critique love (hate it) and affirm it. Multidisciplinary approaches for developing a deeper, more comprehensive understanding of love are discussed.